Moral harassment at work: Between international recognition of its harmful effects and the limits of the classification of the resulting illnesses - Younes, Badreddine (Journal of Human Sciences, 2023)
The world has realized the seriousness of the phenomenon of bullying for the health of workers, on the other hand, the reactions against this phenomenon have varied, so some countries have adopted a response to this phenomenon through legislation, but some of them have adopted a preventive policy, and the question of the classification of diseases resulting from bullying remains unsatisfactory, due to the difficulty of proving the relationship between the forms of harassment and the diseases from which harassed workers may suffer .